Pilot Feasibility Study of Comprehensive Pulmonary Evaluation Following Lung Radiation Therapy. Issue 7 (October 2015) - De, Aliva; Mascarenhas, Leo; Kamath, Sunil; LaRiviere, Alejandro; Goodarzian, Fariba; Keens, Thomas G.; Venkatramani, Rajkumar
Abstract : Background: Symptoms of pulmonary injury following lung irradiation may not manifest clinically in childhood. We performed comprehensive pulmonary evaluation of patients who had received lung irradiation for treatment of cancer. Materials and Methods: Patients underwent a focused history and physical examination, computed tomography of the chest, pulmonary function test, and cardiopulmonary exercise stress test (CPET). Health-related Quality of Life was also measured. Results: Fourteen patients were recruited with median age of 16 years (range, 6 to 21 y). Median time from pulmonary radiation to testing was 5 years (range, 2 to 11 y). Five patients reported pulmonary symptoms. Twelve patients (85.7%) had at least 1 pulmonary function test abnormality. Nine patients demonstrated CPET abnormalities; 7 patients had abnormal pulmonary limitation to exercise, and 5 patients had exercise-induced bronchospasm. The pulmonary limitations included abnormal ventilatory response to exercise in 5 patients, and gas exchange abnormalities in 4 patients. Chest computed tomography demonstrated grade 1-2 radiation-induced lung changes in 4 patients, and grade 3 abnormalities in 1 patient. Conclusions: Significant pulmonary dysfunction was observed in childhood cancer survivors who had received lung irradiation. CPET is feasible in childhood cancer survivors and can be valuable for assessment of pulmonary function and exercise capacity. Abstract : Supplemental Digital Content is available in the text.